Antigenicity and receptor affinity of SARS-CoV-2 BA.2.86 spike - Wang, Qian; Guo, Yicheng; Liu, Liyuan; Schwanz, Logan T.; Li, Zhiteng; Nair, Manoj S.; Ho, Jerren; Zhang, Richard M.; Iketani, Sho; Yu, Jian; Huang, Yiming; Qu, Yiming; et al. (Nature (London), 2023)
A severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron subvariant, BA.2.86, has emerged and spread to numerous countries worldwide, raising alarm because its spike protein contains 34 additional mutations compared with its BA.2 predecessor 1 . We examined its antigenicity using human sera and monoclonal antibodies (mAbs). Reassuringly, BA.2.86 was no more resistant to human sera than the currently dominant XBB.1.5 and EG.5.1, indicating that the new subvariant would not have a growth advantage in this regard. Importantly, sera from people who had XBB breakthrough infection exhibited robust neutralizing activity against all viruses tested, suggesting that upcoming XBB.1.5 monovalent vaccines could confer added protection. Although BA.2.86 showed greater resistance to mAbs to subdomain 1 (SD1) and receptor-binding domain (RBD) class 2 and 3 epitopes, it was more sensitive to mAbs to class 1 and 4/1 epitopes in the ‘inner face’ of the RBD that is exposed only when this domain is in the ‘up’ position. We also identified six new spike mutations that mediate antibody resistance, including E554K that threatens SD1 mAbs in clinical development. The BA.2.86 spike also had a remarkably high receptor affinity. The ultimate trajectory of this new SARS-CoV-2 variant will soon be revealed by continuing surveillance, but its worldwide spread is worrisome. A severe acute respiratory syndrome coronavirus 2 Omicron subvariant, BA.2.86, was found to be no more resistant to human sera than the currently dominant XBB.1.5 and EG.5.1, but it had a remarkably higher receptor affinity.